Evaluating Player Experience in Stealth Games: Dynamic Guard Patrol Behavior Study - Al Enezi, Wael; Verbrugge, Clark (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2023)
In stealth games, guard patrol behavior constitutes one of the primary challenges players encounter. While most stealth games employ hard-coded guard behaviors, the same approach is not feasible for procedurally generated environments. Previous research has introduced various dynamic guard patrol behaviors; however, there needs to be more play-testing to quantitatively measure their impact on players.This research paper presents a user study to evaluate players' experiences in terms of enjoyment and difficulty when playing against several dynamic patrol behaviors in a stealth game prototype. The study aimed to determine whether players could differentiate between different guard behaviors and assess their impact on player experience.We found that players were generally capable of distinguishing between the various dynamic guard patrol behaviors in terms of difficulty and enjoyment when competing against them. The study sheds light on the nuances of player perception and experience with different guard behaviors, providing valuable insights for game developers seeking to create engaging and challenging stealth gameplay.